Analysis of the optical properties of UVA and UVB exposed gelatin-based skin phantom applied with sunscreen using time-domain optical coherence tomography - Templonuevo, John Eros T. (Animo Repository, 2024)
Various tissue-mimicking samples, like cell lines, are used to simulate the optical properties of human skin without subjecting the actual living organism to extensive testing. However, those require continuous monitoring and strict atmospheric conditions to maintain cell viability and proliferation. On the other hand, Gelatin-based Skin Phantoms (GBSP) offer cheaper and more sustainable alternatives to live samples and cell lines. GBSP can simulate the Extinction Coefficient (EC) of human skin by adjusting the concentration of Titanium Dioxide (TiO2), as a scattering agent (Galvez et. al, 2021). Using GBSP samples with 3 varying TiO2 concentrations (0.09%, 0.13%, 0.17%), this study aims to identify which Ultraviolet Radiation (UVR) wavelength will significantly alter GBSP’s EC values. Additionally, 2 types of sunscreen are applied on GBSP samples to compare sunscreen’s photoprotection against UVR. In Bajgar et. al’s study (2021), after a 40-minute exposure time to UVA and UVB lamps, they found a significantly larger decrease in HaCaT Cell Lines (HCL) viability and proliferation after UVB irradiation compared to UVA irradiation. They concluded that the cell lines are more photosensitive to UVB than UVA. However, GBSP samples do not present similar photosensitivity with HCL. There is no significant difference in EC values between GBSP samples exposed to UVA and UVB. Only the sunscreen type and TiO2 concentrations display significant factors altering GBSP samples’ EC values.